TESTING THREE STATISTICAL CRITERIA TO SCREENING S3 FAMILIES BY RECIPROCAL RECURRENT SELECTION IN POPCORN - & Jabouri, Mhomood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Afield experiment was conducted during in fall season 21 /7/2016 to screen 100 top crosses ,which is represented S3 generation, derived from popcorn population AGR-2, After one cycle of reciprocal recurrent selection (RRS). as The genotypes AGR-2 and Suror used vtesters and evaluated with top crosses with control variexy. The experiment was carried out using 10x10 partial balance lattice design with two replications. Three statistical criteria for screening were used, First, standard error, the second duplicated standard error value and the third standard division value. All the values statistical criteria were added to total mean. The results were showed a significant differences among in top crasses this study. Results of first criteria, were included two groups, the first one consisted of 19 progenies, was well of performance to grain yield and popping expansion, second group was consisted of 10 progenies, which reveled well expansion popping and others traits. The results of second criteria were revealed tow group, first one include10 progenies which had the best of performance for grain yield and expansion popping while, another group include 8 progenies were well performance of popping expansion. The third criteria which is indicated that 14 progenies were best popping expansion and three progenies superior in in grain yield per plant.